A Multifunctional MIL-101-NH2(Fe) Nanoplatform for Synergistic Melanoma Therapy - Shang J; Chen Y; Wang F; Yang J; Li Y; Yang L; Liu X; Zhong Z; Yue C; Zhou M (International Journal of Nanomedicine)
Jinlu Shang,1,2,* Yongjun Chen,2,* Fangliang Wang,3,* Jing Yang,2 Yi Li,4 Liuxuan Yang,2 Xiuqiong Liu,1 Zhirong Zhong,5 Chaochi Yue,6 Meiling Zhou2 1Department of Pharmacy, West China Hospital Sichuan University Jintang Hospital, Chengdu, Sichuan, 610400, People’s Republic of China; 2Department of Pharmacy, The Affiliated Hospital, Southwest Medical University, Luzhou, Sichuan, 646000, People’s Republic of China; 3Chongqing Key Laboratory for Pharmaceutical Metabolism Research, Chongqing Pharmacodynamic Evaluation Engineering Technology Research Center, College of Pharmacy Chongqing Medical University, Chongqing, 400016, People’s Republic of China; 4Department of Nuclear Medicine, The Affiliated Hospital, Southwest Medical University, Luzhou, Sichuan, 646000, People’s Republic of China; 5Department of Pharmaceutical Sciences, School of Pharmacy, Southwest Medical University, Luzhou, Sichuan, 646000, People’s Republic of China; 6Department of Traditional Chinese Medicine, The Affiliated Hospital, Southwest Medical University, Luzhou, Sichuan, 646000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Meiling Zhou; Chaochi Yue, Email meilzhou@163.com; yuechaochi18@swmu.edu.cnBackground: Melanoma is an aggressive form of skin cancer, and single-modality treatments often fail to prevent tumor recurrence and metastasis. Combination therapy has emerged as an effective approach to improve treatment outcomes.Methods: In this study, we developed a multifunctional nanoplatform, MIL@DOX@ICG, utilizing MIL-101-NH2(Fe) as a carrier to co-deliver the chemotherapeutic agent doxorubicin (DOX) and the photosensitizer indocyanine green (ICG). MIL-101-NH2(Fe) was synthesized via a hydrothermal method. Drug release was evaluated under different pH conditions, and the photothermal effect was tested under near-infrared (NIR) laser irradiation. Hydroxyl radical and reactive oxygen species generation capacities were quantified. Cellular studies using B16F10 cells assessed cytotoxicity, cellular uptake, migration inhibition, and colony formation suppression. In vivo experiments in melanoma-bearing mice evaluated antitumor efficacy and systemic safety through tumor growth inhibition, histological analyses, and toxicity assessments.Results: MIL@DOX@ICG exhibited a uniform octahedral structure with a particle size of approximately 139 nm and high drug loading efficiencies for DOX (33.70%) and ICG (30.59%). The nanoplatform demonstrated pH-responsive drug release and potent photothermal effects. The generation of hydroxyl radicals via the Fenton reaction and reactive oxygen species production under NIR laser irradiation by MIL@DOX@ICG were confirmed. In vitro assessments revealed significant cytotoxicity of MIL@DOX@ICG against B16F10 cells under NIR laser irradiation, with improved efficacy in inhibiting cell proliferation and migration. In vivo studies confirmed the superior antitumor efficacy of MIL@DOX@ICG + NIR treatment, synergistically harnessing chemotherapy, photothermal therapy, photodynamic therapy, and chemodynamic therapy effects while maintaining excellent biocompatibility.Conclusion: Our findings underscore the potential of MIL-101-NH2(Fe) nanoparticles as a versatile and effective platform for synergistic melanoma therapy, offering a promising strategy for overcoming the limitations of conventional treatment modalities.Keywords: melanoma, MIL-101-NH2(Fe), chemotherapy, photothermal therapy, photodynamic therapy, chemodynamic therapy